A study on feto-maternal outcome in instrument assisted vaginal deliveries - S., Sahana Shankari; Jaget, Nirmala; Sekar, Sindhujha; P. B., Hiremath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Operative Vaginal delivery (OVD) is performed with either forceps or vacuum used in second stage labour when there is maternal or fetal distress. A successful instrument assisted vaginal delivery can reduce the incidence the incidence of caesarean rates and its associated morbidity and mortality. It can be effective and safe when applied according to the individual patients indications. Methods: A retrospective study was carried out in patients who has undergone instruments assisted vaginal delivery in SVMCH&RC during the year 2021-2023 and their data was obtained from medical record and delivery register at the hospital. The data obtained from Sri Venkateshwaraa Medical College Hospital and Research Centre Puducherry is compared with previously published studies. Results: Out of 2022 deliveries 67 were instrument assisted vaginal deliveries in which majority of participants were primigravida aged between 21-30 years. The most common maternal indication was maternal exhaustion with inadequate expulsive efforts. Around 97% of newborn delivered by assisted vaginal delivery had an apgar score >6 at 1 minute. The complications have been reported in both vacuum and forceps assisted vaginal deliveries with slight increase in numbers on forceps assisted vaginal deliveries. Conclusions: In this study after reviewing current various articles, it is proposed that surgeons prefer vacuum over forceps assisted vaginal delivery as it can provide better outcome in both mother and fetus in terms of both complications and its associated maternal and newborn morbidity and mortality. However, it should be applied according to individual patients indications, to reduce the caesarean section delivery rates.